ANALISA SENSITIVITAS RESPON KONSUMEN DARI EKSTENSIFIKASI MEREK (BRAND EXTENSION) PADA SABUN MANDI CAIR MEREK CITRA (Studi pada Mahasiswa Universitas Muhammadiyah Purwokerto) - Puput Alviana; Agung Miftahuddin (Media Ekonomi, 2016)
The success stems soap brand image in the market can lead consumers to buy shower gel Citra brand image. Shower gel Citra brand image is the result of the expansion of the brand (brand extension) conducted by PT. Unilever Indonesia from old products, namely soap rod Citra brand image. The results showed that consumers are sensitive to the presence of soap brand extension rod for shower gel and direction of consumer response showed positive results of toilet soap brand extension rod Citra brand image to shower gel Citra brand image with a sensitivity of 2.27. Changes in brand extension stimuli (brand extension) of soap rod brand image to shower gel brand image based on product attributes and Hierarcy stages of addressing the effect of positive values 321. A positive value shows that the stimuli are attached to the liquid bath soap brand image got a higher response from consumers in comparing stem bath soap brand image that has long existed before. Keywords: sensitivity, response, brand extension.